Evaluation of the commercially available HepProbe kit for detection of hepatitis B virus DNA in serum. - Valentine-Thon, E (1990)
The commercially available HepProbe kit involving the use of a 32P-labeled RNA probe was evaluated for its sensitivity, specificity, and reproducibility in detecting hepatitis B virus (HBV) DNA in patient serum by dot blot hybridization. The level of detection was 0.3 pg, corresponding to 3 x 10(4) genomes in 50 microliters of serum. A total of 181 serum samples were tested; 53 (82%) of 65 patients positive for both hepatitis B surface antigen and hepatitis e antigen were positive for HBV DNA compared with only 12 of 74 (16%) hepatitis B surface antigen-positive but hepatitis e antigen-negative individuals. In addition, among all patients positive for HBV DNA, there was a statistically significant correlation between the concentration of HBV DNA in serum and the presence or absence of hepatitis e antigen. None of the 42 hepatitis B surface antigen- and hepatitis e antigen-negative patients tested was positive for HBV DNA. Reproducibility was 87%, with all discordant results representing borderline positives. The results indicate that HepProbe can be employed as a sensitive and reliable assay for HBV DNA in patient serum.